FAKTOR PRODUKSI PADA BERBAGAI BENTUK PASAR OUTPUT DAN INPUT DALAM PERSPEKTIF ISLAM - Fatikul Himami (Maliyah : Jurnal Hukum Bisnis Islam, 2014)
In Islamic economics we not only learn but also the social individual religious man with talent. This is due to the high demand and lack of means, there arises a problem of economics. This problem is essentially the same in both the modern economy and Islamic economics. However, differences arise pleased with the choice. Islamic economics is controlled by the basic values of Islam and modern economics is dominated by the self-interest of the individual. Therefore we expect all economic actors in the country for a moment think that is more attractive to immediately make a real change in the economic system that leads to the welfare of mankind and keadialn. In modern economics is a matter of choice really depends on the kinds of behavior of each individual. They may or may not take into account the requirements of society. But in Islamic economics, we are not in a position to distribute the resources at will. In this case there is a serious limitation based on the provisions Scriptures of the Qur'an and Sunnah upon the power of the individual. In Islam, social welfare is maximized when economic resources are also allocated such that the rearrangement of the situation, no one better by making someone else worse in the framework of the Qur'an or the Sunnah.